Hubungan Dukungan Suami dengan Kepatuhan Mengkonsumsi Tablet Tambah Darah pada Ibu Hamil di Wilayah Kerja UPTD Puskesmas Penarik Mukomuko - Winda Amallia; Febra Ayudiah; Meita Tria Saputri (Student Scientific Journal, 2026)
Fe is essential for the formation of red blood cells and hemoglobin, which are vital for supplying oxygen and nutrients to all cells in the mother's and fetus's bodies. The WHO and the Indonesian Ministry of Health recommend that pregnant women take Fe tablets for at least 90 days during pregnancy and up to 40 days after giving birth. Husband support plays an important role in increasing pregnant women's compliance with taking Fe tablets. This study aims to determine a correlation between husband support and compliance with Fe supplement consumption among pregnant women in the working area of UPTD Penarik Mukomuko Health Center. This study uses a quantitative research method with an analytical design and a cross-sectional approach. The population and sample in this study consisted of all 43 respondents who were pregnant women in their third trimester, using total sampling technique. The research instrument used a questionnaire. Data analysis was performed using univariate and bivariate analysis. The results of the univariate analysis showed that most respondents whose husbands were supportive and compliant in consuming Fe tablets numbered 26 people (60.5%). Respondents whose husbands were not supportive and not compliant in consuming Fe tablets numbered 17 people (39.5%). The results of bivariate analysis using the chi-square statistical test showed a p-value = <.001 (<α 0.05), so it can be concluded that there is a correlation between husband support and compliance with Fe tablet consumption among pregnant women in the working area of UPTD Penarik Mukomuko Health Center. The researcher recommends that husbands provide support and motivation to pregnant women to comply with Fe tablet consumption. The health center should improve the effectiveness of its services, monitoring, and counseling on the importance of Fe tablets for pregnant women.